Ayat-Ayat Pendidikan Tentang Potensi Manusia Dalam Pengetahuan (Knowladge), Ilmu Pengetahuan (Sains), Filsafat, Dan Agama - Wan Elnayla Azzahra Reza; Zahara Tul Husni; Elsya Frilia Ananda N; Bias Tirta Bayu; Wismanto Wismanto (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Humans always strive to develop their potential. One way to develop this potential is through lifelong education and philosophy. Education is given or held in order to develop all human potential in a positive direction. Because by continuing to develop ourselves, we will undoubtedly become complete human beings with the various potentials that we have. What differentiates humans from other creatures is science, because with science humans can always differentiate between good and bad, right and wrong and so on. Philosophy and religion are essentially two different domains, in fact there are often differences of opinion between the two, but in fact the two are things that are interconnected and combined to understand the nature of science in both. The research method used is a causal-effectual analysis model using a rational approach based on the results of a literature review. The aim of the research is to find out and how to develop the potential that exists in humans related to education, namely, in knowledge, science, philosophy and religion. Knowledge should be something very vital that must receive attention in order to lead to a better life. Knowledge itself has various forms in the form of ordinary knowledge, religious knowledge, philosophical knowledge and scientific knowledge.